Dry needling with electrical stimulation for the treatment of a pediatric patient with spastic cerebral palsy: a case report - Temrah Okonski; Jan Dommerholt (Exploration of Neuroprotective Therapy, 2022)
The patient was a 6-year-old child with spastic quadriplegic cerebral palsy (CP) categorized with the gross motor function classification system (GMFCS) as a level IV and a Modified Modified Ashworth Scale (MMAS) of 2 for the bilateral hamstring and hip adductor muscles, and 3 for the bilateral gastrocnemius muscles. This patient’s limited range of motion significantly affected the caregiver’s ability to perform activities of daily living (ADLs). Dry needling (DN) is considered a standard treatment (TX) when treating adults with poor range of motion. This article aims to place intramuscular electrical stimulation (IMES), the delivery of an electrical current through a monofilament needle into targeted trigger points (TrPs) within the context of treating children with spastic CP. Following IMES TXs over 32 months that totaled 12 left hamstring TXs, 13 right hamstring TXs, 13 hip adductor TXs, 21 left gastrocnemius TXs, and 18 right gastrocnemius TXs, the patient demonstrated an increase in passive range of motion (PROM) of the hamstring, hip adductors, and gastrocnemius muscles. These gains equated to ease in ADLs. Both the Pediatric Evaluation of Disability Inventory (PEDI, PEDI-Caregiver Assistance Scale) and the Goal Attainment Scale (GAS) demonstrated decreased caregiver burden. The child’s GMFCS level and the MMAS did not change. Further data collection related to treating children with spasticity using IMES is indicated to validate this type of TX with this patient population.